Enlivening faith: music, spirituality and Christian theology - Boyce-Tillman, June; Roberts, Stephen B.; Erricker, Jane (Music and spirituality, 2019)
The relationship between Christian theology and music has been complex since the early days of the Church. In the twentieth century the secularization of Western culture has led to further complexity. The search for the soul, following Nietzsche's declaration of the Death of God has led to an increasing body of literature in many fields on spirituality. This book is an attempt to open up a conversation between these related discourses, with contributions reflecting a range of perspectives within them. It is not the final word on the relationship but expresses a conviction about their relationship. Collecting together such a variety of approaches allows new understandings to emerge from their juxtaposition and collation. This book will contribute to the ongoing debate between theology, spirituality, culture and the arts. It includes contexts with structured relationships between music and the Church alongside situations where spirituality and music are explored with sometimes distant echoes of Divinity and ancient theologies reinterpreted for the contemporary world.